MANAGEMENT PROBLEMS OF TURKISH BUSINESSES in AFGHANISTAN: THE CASE OF KABUL AND MAZARISHARIF - Khurshid, Jamshid (Archives of Business Research, 2016)
Economic, political, social and technological changes worldwide have reached to massive sizes. Together with mass communication, markets have expanded and dimensions of competition have increased accordingly. The present study was conducted to identify management problems experienced by Turkish businesses operating in Afghanistan. Besides, basic problems of Turkish businesses in Afghanistan inflicted from special conditions of Afghanistan were also identified as another objective of the present study. Within the scope of these objectives, general characteristics of Turkish businesses operating in Kabul and Mazari Sharif towns of Afghanistan were determined and basic and management problems experienced by these businesses were investigated. According the research results, basic problems of Turkish businesses were gathered under 4 factors, namely as financial problems; security and infrastructure problems; economic, legal and technical problems; bureaucratic problems. The management problems of executives of Turkish businesses were also gathered under 4 groups as of problems related to planning function; problems related to controlling function; problems related to directing function and problems related to coordinating function of management.